Why physicians teach: giving back by paying it forward. Issue 8 (7th July 2015) - Steinert, Yvonne; Macdonald, Mary Ellen
<x xml:space="preserve">Abstract</x> Context Despite the pace and intensity of the in‐patient clinical setting, physicians carve out time for teaching medical students and residents. Objectives The goal of this study was to explore what it means for physicians to teach students and residents in the in‐patient setting. Methods We conducted semi‐structured interviews with 15 practising physicians from the departments of internal medicine, surgery and paediatrics in three university teaching hospitals at McGill University, using an interpretive phenomenological methodology. Results Five themes elucidated the meaning of teaching for physicians in the in‐patient setting: (i) teaching was perceived as an integral part of their identity; (ii) teaching allowed them to repay former teachers for their own training; (iii) teaching gave them an opportunity to contribute to the development of the next generation of physicians; (iv) teaching enabled them to learn, and (v) teaching was experienced as personally energising and gratifying. Participants were morally and socially motivated to give time and effort through teaching (e.g. to pay forward their own privilege and thereby help to develop the next generation); teaching also gave them a sense of personal fulfilment (e.g. by allowing them to mould young minds and leave a legacy). Conclusions This study holds a number of implications for medical education with relevance to the recruitment and retention of clinical teachers, recognition of clinical teaching, and evidence‐informed faculty development. The findings also suggest that teaching in an academic setting can bring joy and fulfilment to practising physicians.